Perkembangan dan Pola Sektor Pertanian di Kabupaten Dharmasraya - Syahrial; Dian Fauzi; Azmi Fajri (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2023)
The agricultural sector is the largest contributor to the Gross Domestic Product in boosting the economy in Dharmasraya District. In Dharmasraya District, West Sumatra Province, this research was conducted using the analysis tool Entopian Diversity Index and Klassen Typology. These results indicate that the agricultural sector in Dharmasraya Regency has not developed. Paddy, peanuts, rubber and palm oil are rapidly growing commodities that dominate the agricultural economic growth of Dharmasraya District.